Kinetics, crystallization, and structural elucidation of thermostable D311E T1 lipase variant from Geobacillus zalihae - Ruslan, Rudzanna (2013)
T1 lipase from Geobacillus zalihae is a thermophilic enzyme with an optimum temperature of 70 oC at pH 9 and stable up to 65 oC. By introducing an additional ion pair, T1 lipase was believed to be stable at high temperature. Thus, further study of D311E lipase variant are required to determine the effect of ion pairs on T1 stability. The aims of this work are to analyse the kinetic properties and characterise the D311E lipase variant, to optimise crystallisation conditions and to elucidate the 3-D structure of crystallised D311E lipase. This involved a few purification steps,characterisation, kinetic analysis, crystallisation and structural elucidation processes. Wild-type T1 and variant D311E lipases were successfully purified in a series of purification steps. The recovery of wild-type T1 was 22.37 % with the purification fold of 5.16. Meanwhile, the final yield and fold of D311E lipase was 15.71 % and 10.56, respectively. The purification fold of D311E lipase variant was higher than wild-type T1 lipase due to higher specific activity of purified D311E lipase. Purified lipases were used for characterisation and crystallisation. The wild-type T1 and D311E lipase variant had an optimum temperature of 70 oC. The D311E lipase variant was stable and remaining activity at 70 % with preincubation at 60 oC for 75 min while the wild-type T1 lipase was stable only for 15 min. When the lipases were pre-incubated at 70 oC, the D311E lipase variant was stable and remaining activity at 70 % for 10 h while the wild-type T1 lipase was stable for 6 h. Kinetic studies of T1 and D311E lipase using p-nitrophenyl laurate as substrate was conducted by using Hanes-Woolf plot. For T1, the Km, Vmax and Vmax/Km were 39.03 mM, 5.75 mM s-1 and 0.147 mM s-1 mM-1, respectively while for D311E lipase, the Km, Vmax and Vmax/Km were 14.08 mM, 0.23 mM s-1 and 0.016 mM s-1 mM-1, respectively which shows that the variant has high substrate affinity compared to its wild-type. The circular dichroism spectra of T1 and D311E lipase were analysed as a function of temperature at 220 nm. Tm for T1 and D311E lipase were approximately 68.52 °C and 70.59 °C, respectively. It showed that mutation at D311 increases the stability of T1 lipase and exhibited higher Tm. The D311E also exhibited higher activity and stability compared to T1 lipase. Thus, crystallisation and X-ray diffraction were carried out to ensure the consistency of the results at atomic level. Crystallisation of purified D311E lipase was carried out using sitting drop vapour diffusion and capillary gel tube counter diffusion method. Optimisation of D311E lipase crystallisation was performed in order to see the crystal growth effect by using different buffer pH, protein concentration, salt concentration, and temperature using sitting drop vapour diffusion method. For sitting drop vapour diffusion method, the optimum crystallisation formulation was 1.5 M of NaCl, 0.1 M, MES pH 5.5, 1.35 mg/mL of D311E lipase and 20 oC for growth. The size of the crystal obtained was 0.2 mm x 0.1 mm x 0.1 mm. While in the capillary gel tube counter diffusion,optimum conditions to grow D311E lipase crystal were using 3.0 mg/mL protein with formulation C2-21 (Crystal Screen, Hampton Research) at 1 mm of gel tube length. However, the size of crystal grown was approximately 50 μm x 50 μm x 30 μm which is smaller than sitting drop vapour diffusion crystallisation method and therefore, insufficient for in-house X-ray diffraction. Thus, the crystal with optimum condition obtained in sitting drop vapour diffusion method was used for X-ray diffraction. A good quality crystal of D311E lipase was diffracted at 2.1 Å using an in-house Xray beam and this crystal belonged to the monoclinic space group C2 with the unit cell parameters a = 117.32 Å, b = 81.16 Å and c = 100.14 Å. The generated model was further built and refined. The phase problem was solved by using molecular replacement method. T1 lipase crystal structure (PDB ID: 2DSN) was used as the template. The quality of lipase structure was validated using Ramachandran plot and Errat. Hence, the coordinates of D311E crystal structure was deposited to RCSB Protein Data Bank under PDB ID code 3UMJ. Structural analysis showed the existence of an additional ion pair around E311 in D311E structure which led to the formation of an ion pair network comprising of five amino acid residues (Arg274, Thr278, Gly279, Arg303 and Glu311) connected by seven ion pairs. In conclusion, the presence of the additional ion pair stabilised the formation of inter-connection in D311E and regulates stability of lipase at high temperatures.